APPROXIMATION THEOREMS FOR GENERALIZED COMPLEX SZASZ-KANTOROVICH OPERATOR - Kara, M.; Mahmudov, N. I. (Baku State Univ, Inst Applied Mathematics, 2020)
In this article, we introduced the new type generalized complex Szasz-Kantorovich opera tors. We obtain quantitative estimate in the Voronovskaja's theorem and the exact orders in the approximation of analytic functions without exponential growth conditions for these operators on compact disks.
7th International Conference on Control and Optimization with Industrial Applications (COIA) -- AUG 26-28, 2020 -- ELECTR NETWORK
Keywords: Complex Szasz-Kantorovich Operator; Quantitative Estimate in the Voronovskaja's Theorem; Exact Estimates